Função cardíaca e metabolismo de machos e fêmeas de Rhinella icterica no período reprodutivo - Salla, Raquel Fernanda (2017)
Considering the absence of studies on the cardiac function of distinct sexes of native anuran amphibians, the present study proposed to compare the basal heart rate (fh) and the importance and participation of the main proteins involved in the excitation-contraction coupling of each sex in Rhinella icterica species: the Na+/Ca2+ exchanger (NCX), the sarcoplasmic reticulum Ca2+ ATPase (SERCA), its advisory protein phospholamban (PLB), and the Na +/K+ ATPase membrane protein. In addition, the analysis of the basal metabolic rate of the animals verified if the cardiac characteristics are related to the metabolic level of each sex in this species. For this, in vitro experiments with ventricular cardiac strips treated with rianodine were performed, which demonstrated a significant reduction of the contraction force, indicating a relevant partitioning of the sarcoplasmic reticulum in both genera of this species, but more evident in males. LiCl treatment demonstrated a greater dependence of females on the role of NCX as a source of calcium for contraction, and even more on relaxation mechanisms. The ouabain protocol demonstrated a significant importance of Na +/K+ ATPase in both sexes, especially in the relaxation mechanisms. Corroborating these results, the expression of SERCA and PLB was higher in males, and NCX showed higher expression in females. The analyzes of basal metabolic rate of males also revealed higher values, which indicates a possible relationship between the metabolic rate of each sexual gender and their cardiac function adapted to each metabolism in this species. Cardiac function, therefore, varies according to sex in R. icterica, which represents an unprecedented finding in the comparative physiology of anuran amphibians.